Answer:
-1, 1 and 3.
Step-by-step explanation:
Let the integers be n, n + 2 and n + 4, then
6( n + n+2 + n + 4) = 18
6(3n + 6) = 18 Divide through by 6:
3n + 6 = 3
3n = -3
n = -1
So the integers are -1, 1 and 3.
Answer:
<h2>the way its set up its kind of confusing </h2>
Step-by-step explanation:
Answer:
-37
Step-by-step explanation:
Simplifying
74 + 2x = 0
Solving
74 + 2x = 0
Move all terms containing x to the left, all other terms to the right.
Add '-74' to each side of the equation.
74 + -74 + 2x = 0 + -74
Combine like terms: 74 + -74 = 0
0 + 2x = 0 + -74
2x = 0 + -74
Combine like terms: 0 + -74 = -74
2x = -74
Divide each side by '2'.
x = -37
Simplifying
x = -37
The standard conversion toolbox:
x=rcos(θ)
y=rsin(θ)
Here r=7csc(θ)
so
x=7csc(θ)*cos(θ)=7cos(θ)/sin(θ)=7cot(<span>θ)
y=7csc(</span>θ)*sin(θ)=7sin(θ)/sin(<span>θ) = 7
therefore the rectangular coordinates are (7cot(</span><span>θ), 7)</span>
The answer is A. -3x2 - 6x - 7